Reformulation markers in academic discourse : a cross-linguistic and cross-disciplinary study - Šinkūnienė, Jolanta (Array, 2019)
Using quantitative and qualitative approaches alongside contrastive analysis, this paper investigates distribution frequency and functions of reformulation markers employed in academic discourse in two languages (English and Lithuanian) and three science fields (humanities, medicine, technology). The English language data is taken from the academic language sub-corpus of the Corpus of Contemporary American English, while the Lithuanian language data comes from the Corpus Academicum Lithuanicum, a specialised synchronic corpus of written academic Lithuanian. The results show that it is the humanities scholars who employ reformulation markers most frequently in both languages. They also employ a wider range of reformulation markers and use them in more diverse ways than scholars in the hard fields. The most frequent function of reformulation markers irrespective of language and science field is the interpretation of explicit content. The analysis highlights the importance of the discipline and genre in the distribution and use of reformulation markers.